2019
DOI: 10.1155/2019/9381346
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Opioid Dependence with Flexible Doses of Injectable Prolonged Release Buprenorphine

Abstract: Opioid dependence (OD) may be effectively treated with well-evidenced regimens including psychosocial and pharmacotherapeutic interventions. Treatment has benefits but also limitations including risk of diversion, impact of mandatory daily supervision, and stigma. An injectable prolonged release buprenorphine with flexible dose options has recently been approved by the European Commission and is available in the UK and other European Countries. Initial positive treatment experience in patients with different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…A structured interview guide was developed following validated examples 18 and published case studies describing PRB treatment outcomes. 19 The guide provided a detailed description of the interview to ensure consistency during discussions. The initial section of the guide focused on satisfaction with PRB treatment, the second section of the guide focused on recovery status.…”
Section: Methodsmentioning
confidence: 99%
“…A structured interview guide was developed following validated examples 18 and published case studies describing PRB treatment outcomes. 19 The guide provided a detailed description of the interview to ensure consistency during discussions. The initial section of the guide focused on satisfaction with PRB treatment, the second section of the guide focused on recovery status.…”
Section: Methodsmentioning
confidence: 99%
“…Most participants (approximately 60%) were male and of Caucasian ethnicity (>50%), with the remainder comprising other ethnic backgrounds including Asian, Black, Hispanic, and Latino. Occupational status was not consistently reported across all studies; however, for those that did, employment (full or part-time) ranged from 32% to 56% (D'Agnone, 2019;Frost et al, 2019;Gilman et al, 2018;Haight et al, 2019;Larance et al, 2020;Ling et al, 2019Ling et al, , 2020Lofwall et al, 2018;Saunders et al, 2020).…”
Section: Participant Informationmentioning
confidence: 98%
“…Seven studies (D'Agnone, 2019;Farahmand et al, 2020;Frost et al, 2019;Haight et al, 2019;Ling et al, 2019Ling et al, , 2020Lofwall et al, 2018) reported on outcomes of LAIB treatment. Eight studies evaluated LAIBnaïve participants' perspectives (Gilman et al, 2018;Larance et al, 2020;Neale et al, 2018aNeale et al, , 2018bNeale et al, , 2019aNeale et al, , 2019bSaunders et al, 2020;Tompkins et al, 2019).…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations